Spatial distribution characteristics and influencing factors of intangible cultural heritage in Southwest China - He, Yinchun; Shi, Xiaoli; Zeng, Bindan; Wang, Jinwei (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2023)
Taking 614 national intangible cultural heritages in Southwest China as the research object, the spatial distribution characteristics and influencing factors of these heritages were analyzed by using the methods of nearest proximity index, kernel density, geographical concentration index,geographical detector and buffer zone analysis. The results show that:（1） There are significant differences in the spatial distribution of intangible cultural heritage types in Southwest China, specifically, more traditional skills and dances, and least traditional sports, recreational arts and acrobatics; The spatial distribution of types show obvious condensation characteristics, among which the heritages of traditional skills and medicine show obvious condensation characteristics, while the heritages of traditional sports,recreational arts and acrobatics tend to be uniform;（2） Southwest intangible cultural heritages presents global feature of "more in the east and less in the west", forming a spatial distribution pattern o